pH of soil of Majalgaon command area (Jayakwadi project stage-III), India - Kadam, S G; Ugle, B J; Rathod, G M; Pathan, D M; Bhambe, P R (Current Botany, 2012)
Present paper deals with the study of pH of soil of Majalgoan command area, India. pH varied from 7.55 to 8.98 in different soil types and showed increased trend with depth in most of the profiles.